Levetiracetam - epilepsy treatment, pharmacokinetics, mechanism of action, interaction and toxicity - Piotr Kozłowski; Wioleta Czępińska-Ćwik; Magdalena Kozłowska; Karolina Kozłowska (Kazimierz Wielki University, 2015)
Kozłowski Piotr, Czępińska-Ćwik Wioleta, Kozłowska Magdalena, Kozłowska Karolina. Levetiracetam - epilepsy treatment, pharmacokinetics, mechanism of action, interaction and toxicity. Journal of Education, Health and Sport. 2015;5(4):143-150. ISSN 2391-8306. DOI: 10.5281/zenodo.16694 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A143-150 https://pbn.nauka.gov.pl/works/553762 http://dx.doi.org/10.5281/zenodo.16694 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2015. Revised 27.03.2015. Accepted: 27.03.2015.   LEVETIRACETAM - EPILEPSY TREATMENT, PHARMACOKINETICS, MECHANISM OF ACTION, INTERACTION AND TOXICITY   Piotr Kozłowski1, Wioleta Czępińska-Ćwik2, Magdalena Kozłowska3, Karolina Kozłowska4   1 Katedra i Zakład Anatomii Prawidłowej Człowieka, UM w Lublinie 2  Klinika Chorób Wewnętrznych, 1 Wojskowy Szpital Kliniczny z Polikliniką w Lublinie 3 Katedra i Zakład Farmakologii doświadczalnej i Klinicznej, UM w Lublinie 4 Instytut Filologii Angielskiej, KUL   Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com   Abstract   Epilepsy is a common chronic neurological disorder that requires a long-term antiepileptic drug therapy. Epilepsy affects approximately 1% of the world's population, so about 50 million people worldwide have epilepsy. It more likely occurs among children and people over the age of 65. This chronic condition is characterized by recurrent, unprovoked epileptic seizures. Although there are many innovative methods of seizure control, such as neurosurgery, vagal nerve stimulations (VNS) and ketogenic diet, pharmacology is most forceful method of epilepsy treatment. Unfortunately, anticonvulsant drugs are not always effective; the number of non-responding patients is higher than 30% [2,25,29,31].             Levetiracetam (LEV) is one of the newest AEDs, marketed worldwide only since 2000 [29]. This novel antiepileptic drug has a unique and non-standard mechanism of action. The structure of LEV is similar to the prototypical nootropic drug piracetam. Its novel mechanism of action is connected with the synaptic vesicle protein SV2A in the brain. The elimination plasma half-live of LEV is approximately from 6 to 8 hours among adults. About 66% of the drug is excreted unchanged and 27% as inactive hydrolysis product [12]. LEV is mainly removed by the kidneys so that elimination parallels kidney function (renal clearance: 0,6 ml/min/kg) [3,12,32]. LEV was found to be well tolerated and effective in all types of seizures in adults and children [18]. It can be also used in combinations with other AEDs. The drug may also be useful in treatment of Lennox-Gastaut syndrome [9].             This article reviews available published data on LEV in the treatment of adults and children, including information about LEV`s pharmacokinetics, chemistry, mechanism of action, interactions and toxicity.   Key words: levetiracetam, antiepileptic drugs, seizures, epilepsy.